Economic transition and international business : managing through change and crises in the global economy - Milliot, Eric; Nivoix, Sophie (Routledge frontiers in the development of international business, management and marketing, 2020)
Economic Transition and International Business brings together academic experts in International Business and sheds new light on the international phenomenon of transitions in the worldwide economy. It includes both academic investigations as well as in-depth empirical studies. The purpose of the book is to investigate how international transitions reshape the environment, as they reallocate and renew activities, and create new strategies for actors and stakeholders. It provides essential insights into a number of contextual changes that organisations are facing internationally, and is structured around three complementary themes. In the first part, recent economic and financial crises are analysed and presented as revealing transitions for the business world. In the second part, the impact of these transitions is assessed at the level of various key economic players in today's societies (states, business networks, companies, associations, etc.). In the third part, certain decision-making and managerial transitions are retained to illustrate the new deal linked to international transitions. This book is recommended reading for scholars and students in management and economics, as well as international business managers. They will find insightful information, either theoretical or practical, including various countries impacted by socio-economic transitions.